C22. Pathobiology of Copd: Lessons From Inflammatory Mechanisms and Genomic Studies 2011
DOI: 10.1164/ajrccm-conference.2011.183.1_meetingabstracts.a4094
|View full text |Cite
|
Sign up to set email alerts
|

The Unfolded Protein Response (UPR) To Heightened Endoplasmic Reticulum (ER) Stress Is Impaired In The COPD Lung

Abstract: Endoplasmic reticulum (ER) stress, a condition caused by accumulation of unfolded or misfolded proteins in the ER lumen, is Rationale: heightened in the COPD lung as a result of impaired protein degradation. Normally, a highly sophisticated, compensatory response termed the unfolded protein response (UPR) relieves ER stress by up-regulating expression of a multi-gene program which codes for molecules that regulate protein folding, transport, degradation and translation. The present study examined UPR gene expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…We did not detect a robust induction of classical ERSR genes at the level of mRNA following acute CSE; however, 25 of 84 genes on UPR array were mildly up-regulated (not shown). Up-regulation of several ER-resident proteins, such as BiP, PDI, and calreticulin, was demonstrated in the lungs of chronic smokers, but not in patients with COPD (24,48). Up-regulation of Chop protein in multiple human lung cell types, especially in alveolar macrophages, was reported after acute exposure, but the response weakened during chronic exposure (53).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not detect a robust induction of classical ERSR genes at the level of mRNA following acute CSE; however, 25 of 84 genes on UPR array were mildly up-regulated (not shown). Up-regulation of several ER-resident proteins, such as BiP, PDI, and calreticulin, was demonstrated in the lungs of chronic smokers, but not in patients with COPD (24,48). Up-regulation of Chop protein in multiple human lung cell types, especially in alveolar macrophages, was reported after acute exposure, but the response weakened during chronic exposure (53).…”
Section: Discussionmentioning
confidence: 99%
“…This exclusion of the XBP1 branch in response to CS, especially at early times postexposure, correlates with a previously reported CS vapor inhibitory effect on XBP1 splicing in vitro (8, 21). Nevertheless, an increase in the total and spliced forms of XBP1 mRNA was seen in patients with COPD (48). Exposure to Tm that resulted in robust XBP1 splicing in livers caused a marginal 2‐fold increase in XBP1 splicing in lungs.…”
Section: Discussionmentioning
confidence: 99%
“…It is associated with upregulation in the expression of the CHOP and GRP78 which are ERS‐associated markers. 49 Tang et al 31 have demonstrated that these two markers are elevated in COPD models and may be inhibited by SIRT1 which is a response to ERS. They have revealed that treatment with Curcumin significantly reduced CHOP and GRP78 via SIRT1 activation.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has considered elevated ERS as potential pathophysiology of COPD. It is associated with upregulation in the expression of the CHOP and GRP78 which are ERS‐associated markers 49 . Tang et al 31 have demonstrated that these two markers are elevated in COPD models and may be inhibited by SIRT1 which is a response to ERS.…”
Section: Discussionmentioning
confidence: 99%
“…25 A heightened ERS has been suggested as a potential pathophysiology of COPD, associated with increased expression of the ERS-related markers GRP78 and CHOP. 26 GRP78 encodes a member of the heat shock protein 70 family and is a major ER chaperone localized in the lumen of the ER and associated with activation of transmembrane ERS sensors. 27 Under normal conditions, CHOP shows low expression levels, but it is overexpressed in response to ERS-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%